"Housing for all" at the era of financialization; can (post-disaster) cities become truly socially resilient and egalitarian?. Issue 10 (3rd October 2018) - Paidakaki, Angeliki; Parra, Constanza
ABSTRACT: This paper examines the realism of the resilience ambition and process of the U.S. housing system, shedding light on its heterogeneity as well as the financialization currently acting as the driving force in real estate production. The resilience ambition leading to enhanced justice and egalitarianism is understood as the provision and maintenance of post-disaster housing for all within an institutionally diverse landscape of housing policy makers and implementers. Particular emphasis is given to the post-Katrina institutional transformations resulting from multifarious interactions between multilevel institutional structures and a diverse landscape of low-income housing policy implementers – referred as social resilience cells (SRCs) in this paper. The nature and level of these transformations determine the degree to which resilience in its heterogeneous form has been incubated in New Orleans. The paper concludes with a discussion on the macro conditions and bottom-linked governance structures under which all SRCs could be better bolstered in a post-financialization, radicalised neowelfare U.S., and which in turn create possibilities for materialising the resilience ambition.